Effectiveness of Edible Coating, Preservation Temperature and Packaging to the Rancidity and Proteolytic Activity in Dried Mudskipper (Pseudapocryptes Elongatus) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Mudskipper (Pseudapocryptes elongatus) has become a high value species in the markets of Mekong Delta, Viet Nam. Mudskipper aquaculture has potential for coastal aquaculture development and is an alternative to shrimp farming in the Mekong Delta. In terms of nutritional quality of fish, sometimes dry fish have higher quality standards compared to fresh fish. P. elongatus aquaculture has developed rapidly to supply the high demand of domestic consumers. Consumption of dried mudskippers fishes has increased during recent years as consumers have become more aware of its nutritional benefits and of the health concerns associated with other meat products. However the dry-salted mudskippers are not stable at normal preservation by rancidity and proteolytic activity because they have too much oil as well as protease enzyme in their abdomen. Edible coating provide a replacement and fortification of the natural layers at the product surfaces to prevent moisture losses, gas aromas and solute movements out of the food, while selectively allowing for controlled exchange of important gases. Biodegradability, barrier properties, biocompatibility, and edibility as well as being nontoxic and non-polluting are a few advantages of edible films and coatings over plastic packages. Preservation temperature and packaging method also influenced to rancidity and proteolytic activity in the dried mudskippers (Pseudapocryptes elongatus). Objective of the current research studied the feasibility of sodium alginate coating in preservation of dried mudskipper (Pseudapocryptes elongatus). The dried mudskippers were treated by different concentration of sodium alginate (1.0%, 1.5%, 2.0%, 2.5%, 3. 0%). The effectiveness of sodium alginate coating was based on quality changes of dried mudskippers such as lipid oxidation: Peroxide value (mEqO2/ kg), Thiobarbituric acid (mg maloaldehyde/ kg); proteolytic changes: total volatile base (TVB-N, mg N/100 g) nitrogen content and trimethylamine (TMA, mg N/100 g). All treated samples were monitored during 12 months of storage at ambient temperature in 3 months of interval sampling. Results revealed that the coating of 2.5% w/w sodium alginate, 4oC in vaccum bag could control microbial spoilage and lipid oxidation of the dried mudskippers. By this approach, the dried mudskippers (Pseudapocryptes elongatus) are stable at normal environment for 12 months. The study indicated that the edible coating could be commercially utilized to prolong the shelf‐life of this oil fish. The improvement in the quality of the seafood products is achieved through inhibition of proteolytic reaction, reduction of lipid oxidation reduction and enhancement of sensorial attributes. Keywords: Pseudapocryptes elongatus, Sodium alginate, Proteolytic reaction, Lipid oxidation, Shelf-Life.